Strategi Program Sosialisasi Per-RT (SPROSPERT) sebagai upaya penanggulangan masalah distribusi zakat fitrah di Desa Mojopurogede, Kec. Bungah, Kab. Gresik - Fanani, Muhammad Fithrah (Maliki Interdisciplinary Journal, 2024)
Zakat is obligation carried out by all Muslims. the Republic of Indonesia, everybody specifically manages zakat nationally is the National Amil Zakat Agency (BAZNAS). The establishment UPZ is effort facilitate the management and distribution zakat to residents who really need it in an area. UPZ is unit based Decree the Chairman of National Amil Zakat Agency Number 25 of 2018 concerning Guidelines for Management Zakat Unit of the National Amil Zakaah. Mojopurogede Zakat Collection Unit in carrying out duties in village community, encounters several problems that must resolved to realise better management and distribution of zakat. Some of the problems in Mojopurogede village community are zakat fitrah that is not distributed through the committee so distribution of zakat is less coordinated and less targeted. The RT Socialisation Program Strategy (SPROSPERT) is strategy carried out to overcome the ignorance of the Mojopurogede village community Zakat Collection Unit (UPZ) which is authorized to manage zakat. The mechanism of socialisation program is socialise UPZ to community through gatherings that are often Mojopurogede villagers, such as PKK, Jama’ah mosque, RT Meetings, IPNU-IPPNU, Karang Taruna and others. The ultimate goal of this programme is the distribution of zakat can be channeled properly and directed.